Paleomagnetism in Lake Pannon: Problems, Pitfalls, and Progress in Using Iron Sulfides for Magnetostratigraphy - Nick A. Kelder; Karin Sant; Mark J. Dekkers; Imre Magyar; Gijs A. vanDijk; Ymke Z. Lathouwers; Orsolya Sztanó; Wout Krijgsman (Geochemistry, Geophysics, Geosystems, 2018)
Abstract Dating of upper Miocene sediments of the Pannonian Basin (Hungary) has proven difficult due to the endemic nature of biota, scarcity of reliable radio isotopic data, and generally inconsistent magnetostratigraphic results. The natural remanent magnetization (NRM) is mostly residing in greigite (Fe3S4), which complicates NRM interpretation. We reinvestigate the viability of these sediments for magnetostratigraphy using samples from recently drilled well cores (PAET‐30 and PAET‐34) from the Paks region. Significant intervals of the cores contain composite NRM behavior. Thermal demagnetization results include multipolarity (M‐type) samples consisting of a low‐temperature (LT, above ~120 °C), a medium‐temperature (MT), and a high‐temperature (HT) component, within distinct temperature ranges and all exhibiting dual polarities. The LT and HT components have the same polarity and are antiparallel to the MT component. Rock magnetic and scanning electron microscopy results indicate that all magnetic components reside in authigenic greigite. The LT and HT components represent the characteristic remanent magnetization and are of early diagenetic origin. The MT component records a late diagenetic overprint. Alternating field demagnetization cannot resolve the individual components: it yields polarities corresponding to the dominant component resulting in erratic polarity patterns. Interpretation of LT and HT components allows a reasonably robust magnetostratigraphic correlation to the geomagnetic polarity time scale with the base of PAET‐30 at ~8.4 Ma and its top at ~6.8 Ma (average sedimentation rate of ~30 cm/kyr). The base of PAET‐34 is correlated to ~9 Ma and its top to ~6.8 Ma (average sedimentation rate of 27 cm/kyr).